2016
DOI: 10.1682/jrrd.2015.04.0073
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive reserve and executive function: Effect on judgment of health and safety

Abstract: Abstract-Individuals with the same neurological conditions do not necessarily manifest the same behavioral presentation, which suggests differences in resilience and vulnerability among individuals, a concept known as cognitive reserve. This study sought to explore the relationship among cognitive reserve, executive functioning, and health and safety judgment in a sample of older adult inpatients in an extended medical care unit at a Veterans Health Administration hospital. We hypothesized that cognitive reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…[16][17][18][19] Because CR cannot be easily quantified, proxy measures such as premorbid intellectual ability, education, occupational attainment, and leisure activity have been used as surrogate variables and are established as standards of CR measurement in the literature. 20 CR has most frequently been adopted in research on acquired or neurodegenerative conditions, such as Alzheimer's disease, traumatic brain injury, and vascular disease; [21][22][23][24][25][26][27][28] however, CR has only recently been applied to neuropsychiatric disorders, such as schizophrenia, post-traumatic stress disorder, and BP, to help explain variability in symptom severity and neuropsychological correlates. 1,29,30 In one of the few studies examining CR in BP, Forcada and colleagues 31 found that BP participants with lower neuropsychological functioning (in verbal and visual memory and executive functioning) also tended to have lower psychosocial functioning, education, occupational attainment, and leisure activities compared to the control group.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] Because CR cannot be easily quantified, proxy measures such as premorbid intellectual ability, education, occupational attainment, and leisure activity have been used as surrogate variables and are established as standards of CR measurement in the literature. 20 CR has most frequently been adopted in research on acquired or neurodegenerative conditions, such as Alzheimer's disease, traumatic brain injury, and vascular disease; [21][22][23][24][25][26][27][28] however, CR has only recently been applied to neuropsychiatric disorders, such as schizophrenia, post-traumatic stress disorder, and BP, to help explain variability in symptom severity and neuropsychological correlates. 1,29,30 In one of the few studies examining CR in BP, Forcada and colleagues 31 found that BP participants with lower neuropsychological functioning (in verbal and visual memory and executive functioning) also tended to have lower psychosocial functioning, education, occupational attainment, and leisure activities compared to the control group.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions related to executive functions, such as the N-back test and judgment task [ 31 , 32 ] did not reveal significant improvements. This might suggest the need for activities that involve three-dimensional (3D) environments or games that require predicting the surrounding space in a more 3D manner and strategizing [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…16,31 Judgement, cognition, and functioning We found a correlation between function, cognition, and judgement, which strengthens our conclusion regarding probable convergent validity. Accordingly, in the study of Hinrich and colleagues 32 , on the relationship between judgement and functional status and ability to perform independent daily activities in a population with dementia, there is a significant relationship between the level of cognition and the functional state, as well as between the functional state of the person and judgement ability. The researchers found that functional status and cognition were jointly associated with 56% of the variance in judgement.…”
Section: Discussionmentioning
confidence: 99%